Attenuation of ischaemia reperfusion injury by human thioredoxin. Issue 4 (April 1995) - Fukuse, T; Hirata, T; Yokomise, H; Hasegawa, S; Inui, K; Mitsui, A; Hirakawa, T; Hitomi, S; Yodoi, J; Wada, H
Abstract : BACKGROUND--Active oxygen species are thought to play a part in ischaemia reperfusion injury. The ability of a novel agent, human thioredoxin (hTRX), to attenuate lung damage has been examined in a rat model of ischaemia reperfusion injury. METHODS--Twenty eight animals were studied. At thoracotomy the left main bronchus and the left main pulmonary artery were clamped for 75 minutes and the lung was then reperfused for 20 minutes. Phosphate buffered saline was administered intravenously to nine control animals and hTRX (30 micrograms/g body weight) was given intravenously to another group of nine animals. Two experiments were carried out. The first (Exp 1) was a time matched pair experiment (five treated, five controls), and the second (Exp 2) was performed under controlled conditions (four treated, four controls; temperature 25 degrees C, humidity 65%). In another 10 nonischaemic rats and those in Exp 1 biochemical measurements of lipid peroxide, superoxide dismutase, and glutathione peroxide levels were performed. RESULTS--In both experiments rats perfused with hTRX survived longer than controls. In Exp 1 the arterial oxygen tension (PaO2) on air in the hTRX group was higher at 20 minutes than at one minute after reperfusion. In Exp 2 PaO2 at 20 minutes was higher in the hTRX group than in the controls. Lipid peroxide, superoxide dismutase, and glutathione peroxide levels in the control group were higher than in the hTRX group and in the non-ischaemic groups. Histological examination showed less thickening and oedema of the alveolar walls in the hTRX group than in controls. CONCLUSIONS--These results suggest that hTRX is effective as a radical scavenger and can limit the extent of ischaemia reperfusion injury of the lungs of experimental animals.